Uterine Smooth Muscle Tumor of Uncertain Malignant Potential: A Retrospective, Monocentric Cohort Study - Carla Ettore; Giosuè Giordano Incognito; Ferdinando Antonio Gulino; Emanuele Russo; Francesco Cannone; Giuseppe Ettore (Surgeries, 2023)
Smooth muscle tumors of unknown malignant potential (STUMP) represent a group of heterogeneous uterine neoplasms showing worrisome histological features, raising concerns for a malignant behavior, but do not satisfy the diagnostic criteria for leiomyosarcoma. The existing literature remains scarce due to its rarity; therefore, there is no consensus regarding diagnostic criteria, malignant potential, treatment of choice, and follow-up. The authors report their case series to analyze the heterogeneous features of this poorly understood neoplasm. A retrospective, monocentric cohort study of all patients who underwent surgery diagnosed with STUMP at the Garibaldi-Nesima Hospital in Catania from February 2018 to August 2021 was conducted. Each patient’s age at diagnosis, symptoms, surgical treatment, tumor features, postoperative management, and follow-up were recorded. Nine STUMP cases were included. All patients reported menometrorrhagia and pelvic pain. In all women, the tumor lesion was single and intramural, and the mean diameter was 7.5 cm. Four women underwent laparotomic conservative surgery. The mean postoperative follow-up time was 36 months, and recurrences were observed in two patients. In conclusion, STUMP cases should be systematically discussed by tumor boards, pathologists with good expertise in gynecological diseases should examine the histological samples, and close surveillance is mandatory because of the possibility of recurrence or metastasis.